Analisis Perbandingan Prediksi Kebangkrutan Menggunakan Model Altman, Grover, Zmijewski, Dan Springate (Studi Kasus Pada Perusahaan Manufaktur Sub-Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2017-2019) - Cindy Kharisma; Afi Rachmat Slamet; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine and analyze the comparison of the Altman, Grover, Zmijewski, and Springate models in the food and beverage sub-sector manufacturing companies listed on the IDX for the period 2017-2019, as well as to find out and analyze which predictive model is more accurate that can be used. to predict bankruptcy. This study uses 4 samples from 25 populations registered in food and beverage manufacturing companies listed on the IDX for the 2017-2019 period. Sampling using purposive sampling method, namely the sampling method used with certain considerations. Data analysis methods are 1). Calculating financial ratios, 2). Calculating the ratio of the bankruptcy model and 3). Calculate the level of model accuracy. This study finds that in the Altman model there are 1 healthy company and 3 bankrupt companies, in the Grover model there are 2 bankrupt companies and 2 healthy companies, in the Zmijewski model 4 healthy companies, and in the Springate model there are 3 healthy companies and 1 bankrupt company. And the highest accuracy results are the Altman and Springate models with a predictive value of 75%.Keywords: bankruptcy prediction model, Altman, Grover, Zmijewski, Springate